The Influence of Biogeographic Diversity, Climate and Wildlife on the Incidence of Tick-Borne Encephalitis in Croatia - Josip Bago; Linda Bjedov; Marko Vucelja; Kristijan Tomljanović; Nataša Cetinić Balent; Sanja Zember; Josip Margaletić; Oktavija Đaković Rode (Viruses)
Tick-borne encephalitis (TBE) is a common arbovirus infection in Croatia. The aim of the study was to analyse 17 years of data on TBE seroprevalence and acute TBE cases in correlation with winter temperature, precipitation and wildlife abundance to identify possible patterns that may be predictive indicators of TBE incidence. Clinical diagnosis of TBE was confirmed by determining IgM and IgG anti-TBE antibodies. Of the 19,094 analysed patients, 4.2% had acute TBE, significantly more often in older age (p < 0.001) and male gender (p < 0.001). Overall seroprevalence of TBE among the tested population was 5.8% and varied annually from 2.8% to 10.7%. The mean acute TBE incidence rate was 1.1/100,000 population with significant regional differences: 1.7/100,000 in the continental vs. 0.2/100,000 and 0.5/100,000 in the Mediterranean and Alpine regions, respectively. A particularly high incidence of 3.1/100,000 was recorded in northern Croatia. TBE displayed a seasonal pattern, peaking in June and July. Moderate negative correlations were observed between TBE acute cases and winter temperatures from December to February (r = −0.461; p = 0.062), relative rodent abundance (r = −0.414; p = 0.098) and yearly precipitation from one year before (r = −0.401; p = 0.123). The analysis showed that more acute TBE cases are recorded after a warmer winter and a negative correlation between the abundance of forest Apodemus sp. and the number of TBE cases in the same year.